DEICTIC EXPRESSIONS IN THE HOLY BIBLE OF LOCAL NIAS LANGUAGE - Matias Serius Sarumaha; M. Ali Pawiro; Devi Pratiwy (Universitas Islam Sumatera Utara, 2022)
This research deals with the deictic expressions in the Holy Bible of local Nias language. The objectives of the study are to discuss and identify the deixis in the Holy Bible. The research was conducted by using descriptive qualitative design. The data were the epistle of Paul to Philemon which consist of 25 verses. They were collected and analyzed by using a documentation method. The steps were (1) reading the text, (2) finding and marking the deixis, (3) classifying the types of deixis, (4), finding the data, putting sign and making checklist on it, and (5) drawing the conclusions. The results of this research show that there are five types of deixis found in the epistle of Paul to Philemon in the Holy Bible of local Nias language; they are person deixis, spatial deixis, temporal deixis, discourse deixis, and social deixis. The results also show that the deixis mostly found is the person deixis with the frequency of 65 (70%). The following deixis is social deixis that appears 10 times (11%). The discourse deixis appears with the frequency of 9 (10%) while the temporal deixis appears with the frequency of 7 (7%). The deixis that appears the least is spatial deixis with a frequency of 2 (2%).